Mini conveyor belt using geneva mechanism / Muhammad Hariz Luqman Mohd Huszeine and Suhadiyana Hanapi - Mohd Huszeine, Muhammad Hariz Luqman; Hanapi, Suhadiyana (School of Mechanical Engineering, 2023)
A conveyor belt serves as the carrying medium in a belt conveyor system, which is one of several types of conveyor systems. The system consists of two or more pulleys, with a continuous loop of the conveyor belt rotating around them. At least one of the pulleys is powered, propelling the belt and the materials it carries forward. The powered pulley is referred to as the drive pulley, while the unpowered pulley is known as the idler pulley. This project aims to introduce a conveyor belt system in supermarkets to address the main issue with the current design. Many individuals, such as women, children, and the elderly, face difficulties in handling heavy items, particularly in supermarkets. Thus, the conveyor belt project has been initiated to alleviate the burden of lifting heavy objects for these individuals. The primary objective of the project is to efficiently transport objects from one location to another, while also promoting control, saving time, and conserving energy